KEARIFAN LOKAL MASYARAKAT DAYAK MERATUS DALAM PENGELOLAAN HUTAN SECARA TRADISIONAL DI DESA ATIRAN - Miftahul Anwar; Hafizianor Hafizianor; Asysyifa Asysyifa (Universitas Lambung Mangkurat, 2023)
The people of Atiran Village as the Dayak Meratus tribe are very dependent on the forest, their average livelihood is as farmers who use the forest for farming, gardening and hunting. The importance of forests for the socio-economic life of a society is now felt to be increasing because cultural values in the form of human wisdom in managing nature are believed to be the best way to manage nature. This study aims to examine the material infrastructure aspect of the local wisdom of the Meratus Dayak community in Atiran Village. Data collection was done by field observations and interviews. Respondents were determined by purposive sampling method. Data processing is carried out by inductive qualitative analysis, which provides a general and comprehensive picture of the actual situation. Based on the results of research on local wisdom of the Meratus Dayak community in traditional forest management in Atiran Village, namely the cultivation pattern carried out by the Atiran Village community with a